2013
DOI: 10.1111/ejss.12018
|View full text |Cite
|
Sign up to set email alerts
|

Stability of organic matter in soils of the Belgian Loess Belt upon erosion and deposition

Abstract: Summary Soil erosion has significant impacts on terrestrial carbon (C) dynamics. It removes C‐rich topsoil and deposits it in lower areas, which might result in its stabilization against microbial decay. Subsequently, C‐poor deeper horizons will be exposed, which also affects C stabilization. We analysed factors governing soil organic C (SOC) mineralization in topsoil (5–10 cm) and subsoil (75–100 and 160–200 cm) horizons from two contrasting sites (up‐slope compared with down‐slope) in the Belgian Loess Belt;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…Although we did not scale up our results to the landscape level, it is important to know whether the fluxes measured do compare with observed field measurements and make any sense, also in comparison with previous indirect measurements on eroded sediments and soil profile investigations [5], [12]. In the present study, CO 2 efflux rates measured (0.12 to 4.34 g C m −2 day −1 ) were in the range of soil respiration rates from agricultural loess soils [5], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not scale up our results to the landscape level, it is important to know whether the fluxes measured do compare with observed field measurements and make any sense, also in comparison with previous indirect measurements on eroded sediments and soil profile investigations [5], [12]. In the present study, CO 2 efflux rates measured (0.12 to 4.34 g C m −2 day −1 ) were in the range of soil respiration rates from agricultural loess soils [5], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been assumed that dissolved organic matter (DOM) represents a labile part of SOM and that total DOC concentration and especially its easily degradable part resembles soil microbial activity, it has been suggested that a great part of DOM in soil represents a relatively stable by-product of microbial activity (Zhao et al 2008;Wang et al 2013). The movement of DOM is significant to the cycling and distribution of nutrients and carbon within and between ecosystems and contributes to soil forming processes .…”
Section: Water-soluble Organic Carbonmentioning
confidence: 99%
“…Therefore, humus is probably the main source of DOC because of the relatively large amount of humus present in soil relative to that contributed by the microbial biomass or recently deposited plant residues. DOC inputs to soil solution originate from biological decomposition, throughfall or litter leaching, root exudates and from deposition of soot and dust (Wang et al 2013).…”
Section: Water-soluble Organic Carbonmentioning
confidence: 99%
“…The removal of weathered topsoil material from eroding positions, the replacement of eroded SOC, and its burial at depositional sites can potentially lead to a net sink for atmospheric C depending on the fate of the eroded SOC (Harden et al, 1999;Doetterl et al, 2012;Wiaux et al, 2014a). SOC at the depositional site is often regarded as more stable with longer turnover times, depending on microbial activity, environmental conditions (Wang et al, 2013), and biogeochemical characteristics of the transported C fractions. However, areas (or landscapes) with a fast burial can lead to the accumulation (storage) of labile SOC, which is still vulnerable to decomposition if the conditions at the site of burial change (Wiaux et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%